PENGARUH KONSELING GIZI TERHADAP ASUPAN MAKANAN TINGGI PURIN DAN KADAR ASAM URAT PADA PASIEN GOUT ARTHTRITIS DI PUSKESMAS RURUKAN TOMOHON - Ray R. Tamboto; Olfie Sahelangi; Daniel Robert (Jurnal GIZIDO, 2016)
Nutritional counseling is one of the preventive measures in changing attitudes and inincreasing knowledge about gout arthtritis, handling, changing attitudes and consumption offoods high in purines can affect the acid levels urat.Tujuan this study to determine the effectof nutrition counseling to high dietary intake of purines and acid levels urate in gout patientsat the health center arthtritis Rurukan TomohonThis study uses research experiment (quasy Experiment), research experimental is aresearch activity that is conducting the experiment, one group pretest posttest, with a sampleof 34 people were taken from the average visits per month, the data retrieval is done with theinterview to find out the general data of the patient, for the consumption of foods high inpurines using semi FFQ form, and uric acid levels obtained through examinations using uricacid Blood Strip, univariate analysis was conducted descriptively, while bivariate analysisusing the Wilcoxon test with a value of α = 0.05.The results showed that the change in the consumption of foods high in purines of 34respondents this is evidenced by the average value of the mean consumption of purine or71.49 g / day and after counseling, namely 38.71 g / day with a value of p = 0.05 (P = 0.000)it is in line with respondents' levels of uric acid before counseling with an average of 10.4 mg/ dl and after counseling of 8.36 mg / dl with a value of p = 0.05 (P = 0.000) These resultsshow that the influence nutritional counseling to the intake of foods high in purines and uricacid levels in gout patients at the health center arthtritis Rurukan Tomohon